Application of nano silica particles to improve high-temperature rheological performance of tyre pyrolysis oil-modified bitumen - Al-Sabaeei, A. (Taylor and Francis Ltd., 2021)
This study aimed to evaluate the effects of nano silica (NS) particles on the high-temperature rheological properties of tyre pyrolysis oil (TPO)-modified bitumen. Physical tests, short-term aging, temperature sweep test and multiple stress creep recovery (MSCR) test were conducted to evaluate the effects of NS on the high-temperature rheological performance. Results indicate that the inclusion of NS to TPO-modified bitumen displayed significant improvement in rutting resistance before and after aging. Meanwhile, MSCR results showed that the high-temperature performance grade of bitumen was upgraded from PG 64S in the case of base and TPO-modified bitumen to PG 64 V at 10 TPO and 4 NS. Statistical analysis also showed that the effects of NS particles on the rutting performance of TPO-modified bitumen are statistically significant within the confidence interval of 95. These findings present a remarkable enhancement in the high-temperature performance of TPO-modified bitumen. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.